Genome reduction and horizontal gene transfer in the evolution of Endomicrobia-rise and fall of an intracellular symbiosis with termite gut flagellates - Mies, Undine S; Hervé, Vincent; Kropp, Tom; Platt, Katja; Sillam-Dussès, David; Šobotník, Jan; Brune, Andreas (mBio, 2024)
Bacterial endosymbionts of eukaryotic hosts typically experience massive genome reduction, but the underlying evolutionary processes are often obscured by the lack of free-living relatives. Endomicrobia, a family-level lineage of host-associated bacteria in the phylum Elusimicrobiota that comprises both free-living representatives and endosymbionts of termite gut flagellates, are an excellent model to study evolution of intracellular symbionts. We reconstructed 67 metagenome-assembled genomes (MAGs) of Endomicrobiaceae among more than 1,700 MAGs from the gut microbiota of a wide range of termites. Phylogenomic analysis confirmed a sister position of representatives from termites and ruminants, and allowed to propose eight new genera in the radiation of Endomicrobiaceae. Comparative genome analysis documented progressive genome erosion in the new genus Endomicrobiellum, which comprises all flagellate endosymbionts characterized to date. Massive gene losses were accompanied by the acquisition of new functions by horizontal gene transfer, which led to a shift from a glucose-based energy metabolism to one based on sugar phosphates. The breakdown of glycolysis and many anabolic pathways for amino acids and cofactors in several subgroups was compensated by the independent acquisition of new uptake systems, including an ATP/ADP antiporter, from other gut microbiota. The putative donors are mostly flagellate endosymbionts from other bacterial phyla, including several, hitherto unknown lineages of uncultured Alphaproteobacteria, documenting the importance of horizontal gene transfer in the convergent evolution of these intracellular symbioses. The loss of almost all biosynthetic capacities in some lineages of Endomicrobiellum suggests that their originally mutualistic relationship with flagellates is on its decline.IMPORTANCEUnicellular eukaryotes are frequently colonized by bacterial and archaeal symbionts. A prominent example are the cellulolytic gut flagellates of termites, which harbor diverse but host-specific bacterial symbionts that occur exclusively in termite guts. One of these lineages, the so-called Endomicrobia, comprises both free-living and endosymbiotic representatives, which offers the unique opportunity to study the evolutionary processes underpinning the transition from a free-living to an intracellular lifestyle. Our results revealed a progressive gene loss in energy metabolism and biosynthetic pathways, compensated by the acquisition of new functions via horizontal gene transfer from other gut bacteria, and suggest the eventual breakdown of an initially mutualistic symbiosis. Evidence for convergent evolution of unrelated endosymbionts reflects adaptations to the intracellular environment of termite gut flagellates.
Keywords: symbióza; Endomicrobiaceae; metagenom; přenos genů horizontální; fylogeneze; Parabasalia; Phylogeny; Genome, Bacterial; Bacteria; molekulární evoluce; Gastrointestinal Microbiome; Evolution, Molecular; endosymbionts; lateral gene transfer; Isoptera; střevní mikroflóra; Gene Transfer, Horizontal; genom bakteriální; Metagenome; convergent evolution; Animals; zvířata; termites; Symbiosis